Examining the functions of women's violence: Accommodation, resistance, and enforcement of gender inequality. Issue 4 (1st October 2020) - Sichel, Corianna E.; Javdani, Shabnam; Gordon, Nirit; Huynh, Pham Phuong Tram
Abstract: The present study contributes to the literature on the consequences of social inequality through a qualitative examination of the social functions and meanings of violence in the lives of 20 marginalized women. All of the women in the sample were at some point court involved and were victims, as well as perpetrators, of violence. Findings indicate a need to expand the extant theory to address enforcement (i.e., strengthening) of status level, social inequities (e.g., gendered power disparities), adding to the accommodation/resistance paradigm. Consistent with scholarship conceptualizing violence as contextual and gender as a socio-structural variable, results support the need to better understand the ways in which contexts of gendered inequality – and inequality in general – may promote processes through which survivors of violence accommodate, resist, and enforce oppression. Implications for research and practice related to social inequality are discussed.